CLINICAL AND PATHOGENETIC SUBSTANTIATION AND EFFICACY OF INTRAVENOUS APPLICATION OF IMMUNOGLOBULIN IN CHILDREN WITH BACTERIAL PURULENT MENINGITIS - T. E. Makarova; V. P. Molochny (Детские инфекции (Москва))
The article presents data on a study of the effectiveness of intravenous application of immunoglobulin in children with purulent bacterial meningitis of different etiology progressing with pronounced cephaledema. According to our data, the reason for substitution of the immunoglobulin deficiency in patients with purulent bacterial meningitis is clinical syndromes, expressed in points and laboratory indicators of the level of IgG in blood and cerebrospinal fluid of children. The findings give evidence of the efficacy of Intravenous Immunoglobulin application at severe purulent bacterial meningitis accompanied by pronounced immune deficiency, manifested in insufficient synthesis of IgG.